Investigation of anger expression styles of the secondary school students through picture drawing method - (:unkn) unknown (Sakarya University, 2016)
Aim of this study is to find out anger expression styles of secondary school students through drawing pictures. For this reason, students were asked to draw a picture that reflects their thoughts about “how they express themselves when they get angry”. In this qualitative research, content analysis was used. Sample group is comprised of 150 students (50 female, 100 male) between the ages of 15 and 18 high school students from İstanbul (25) and Balıkesir (125) in 2014-2015 academic year. Collected data was analyzed by categorical analysis method. Data was evaluated by calculating frequency (f) and percentage (%). Drawings of the students were categorized by types of anger expression (anger-in, anger-out, anger control) in “;The State Trait Anger Scale” which was developed by Spielberger et. al (1983). The obtained expressions are grouped under 27 titles regarding to similar properties. The most frequent behavior patterns of students when they get angry are respectively “;shouting”, “physical damage”, “swearing” and less often “riding a motorcycle”, “talking to oneself”, “exercising with sandbag”. Then the expressions which fall into the categories of anger-in, anger-out, anger control was evaluated by accounting frequency (f) and percentage (%) in terms of gender and disciplinary penalty variables. © The Turkish Online Journal of Educational Technology.
Keywords: Anger expression; Behavior pattern; Disciplinary penalty; Gender; Picture